Constructing tunable dual active sites on two-dimensional C3N4@MoN hybrid for electrocatalytic hydrogen evolution. (November 2018) - Jin, Huanyu; Liu, Xin; Jiao, Yan; Vasileff, Anthony; Zheng, Yao; Qiao, Shi-Zhang
Abstract: Electrocatalysts are increasingly being used for the production of clean energy. In the past few decades, a wide range of two-dimensional (2D) materials have shown great potential in replacing noble metal catalysts for various electrocatalytic reactions. However, development of alkaline hydrogen evolution technology (a kinetically sluggish process for the conversion of electricity to hydrogen fuel in water electrolyzes) is greatly hindered due to the lack of active candidate materials and mechanistic understanding. In this work, we prepared a hybrid material of 2D graphitic carbon nitride and 2D molybdenum nitride (C3 N4 @MoN) using an interface engineering strategy. The resultant material had a well-designed heterostructure and unique electronic structure. The intimate interaction of both inert graphitic carbon nitride (g-C3 N4 ) and MoN surfaces induced a highly active interface with tunable dual active sites for alkaline HER. Thus, the 2D C3 N4 @MoN hybrid exhibited highly efficient electrocatalytic performance which is better than most of the recently reported non-noble metal catalysts. The combination of experimental characterization with density functional theory calculations shows that the enhanced activity originates from the synergy between the optimized hydrogen adsorption energy on the g-C3 N4 sites and enhanced hydroxyl adsorption energy on the MoN sites. Graphical abstract: fx1 Highlights: A high performance 2D g-C3 N4 @MoN electrocatalyst with dual active sites and unique heterostructure has been synthesized. The activity origin of the catalyst for hydrogen evolution was explored by combining experiments and DFT calculations. This work demonstrated the possibility of tuning multiple active sites simultaneously by constructing a 2D heterostructure.